STUDY OF THE SEEd RESOURCE OF THE INDIAN SAND WHITING SILLAGO SIHAMA (FORSKAL) IN THE PALK BAY - James, P S B R; Soundararajan, R; Rodrigo, Joseph Xavier (Indian Journal of Fisheries, 2011)
The fry and flng^rlings of the Indian sand whiting, Sillago sihama (Forskal), which can serve as seed, have been found to occur in the coastal waters of the Palk bay throughout the year, with at least three months of peak abundance, January, Maf and October. From the year-round availability of these it appears that S. iihama breeds throughout the year, probably with three peak ptiriods, namely, May-June, August-September and November-December. These were observed to be more during day than in night, and more during the receding and low tides than during the incoming tides. The overall abundance was highest during full mdon period. While a direct relationship of the abundance of the Ixy and fingerlings; could be noticed with the increase in temperature and dissolved-oxygen content,; no such relationship was seen with changes in the salinity of sea water.